Complete Genome Sequence of Steroid-Transforming Nocardioides simplex VKM Ac-2033D - Shtratnikova, Victoriya Y. (Genome Announc, 2015)
Nocardioides simplex VKM Ac-2033D is an effective microbial catalyst for 3-ketosteroid 1(2)-dehydrogenation, and it is capable of effective reduction of carbonyl groups at C-17 and C-20, hydrolysis of acetylated steroids, and utilization of natural sterols. Here, the complete genome sequence is reported. An array of genes related to steroid metabolic pathways have been identified.